The decline of the Turkish rule in the Balkans. The political, socio-cultural and military conditions of the end of the Ottoman Empire in Bosnia and Herzegovina - Gibas-Krzak, Danuta (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The aim of this paper is to present a paradigm according to which Bosnia and Herzegovina can be seen as a mirror in which the multifaceted problems of Turkey as the ”sick person of Europe” are reflected. Contributing to the Turkish withdrawal from the Balkans, however, the Ottoman legacy characterized by political and cultural fragmentation permanently became a part of the history of the Balkans and influenced its fate in the 21st century. The author, on the basis of the studies of the American, Polish, Turkish, Bosnian, Serbian and Croatian historians examines the factors that determined the end of Ottoman rule in the Balkans. Bosnia and Herzegovina should be considered the key to the analysis of the Eastern crisis (1875-1878), which proved to be a mere preludes prelude to the end of the Ottoman Empire. The characteristic feature of this province was its permanent insubordination against Turkey, visible in a great number of revolts and uprisings of different provenance against the Turkish government. Already at the beginning of the 17th century, increasing corruption and taxes imposed on the Muslim population led to the first protests against the government. In the 17th century the great uprisings of Bosnian Muslims took place in the following years: 1636, 1650, 1682. In Herzegovina unrest and riots were reported in the following years: 1711, 1727, 1728, 1729, 1732. The Ottoman sources confirmed the occasional participation of the Christian population in those riots. On the one hand, the Muslim feudal lords, who were opposed to the reforms of the Sultan and fought to maintain their privileges, acted against the central power. On the other hand, rebellions had the character of the people’s liberation movement. The largest peasant revolt against the Muslim feudal lords from 1875 in Herzegovina rapidly evolved into the rise of Christian peasants all over Bosnia and Herzegovina, at the same time, the uprising became the South Slavic war of liberation from Turkish rule, contributing to the collapse of the Ottoman Empire.